Energy consumption and economic growth: New insights into the cointegration relationship - Ansgar Belke; Christian Dreger; Frauke de Haan (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
This paper examines the long-run relationship between energy consumption and real GDP, including energy prices, for 25 OECD countries from 1981 to 2007. The distinction between common factors and idiosyncratic components using principal component analysis allows to distinguish between developments on an international and a national level as drivers of the long-run relationship. Indeed, cointegration between the common components of the underlying variables indicates that international developments dominate the long-run relationship between energy consumption and real GDP. Furthermore, the results suggest that energy consumption is price-inelastic. Causality tests indicate the presence of a bi-directional causal relationship between energy consumption and economic growth.
Keywords: C33; O13; Q43; 330; Energy consumption; panel unit roots; panel cointegration; vector error-correction models; Granger causality; Energiekonsum; Wirtschaftswachstum; Kointegration; Kausalanalyse; Energiepreis; Preiselastizität; Schätzung; OECD-Staaten